TAZKIYATUN NAFS SEBAGAI FONDASI PEMBENTUKAN KEPRIBADIAN ISLAMI DALAM DAKWAH DAN KONSELING - Adhim, Fatkhul; Raudoh, Ririn; nurnafilah, Naswa nurnafilah; Ramadhani, Luthfia; Fhadilatun Nisa, Najwa (Jurnal Ilmu Pendidikan Islam, 2025)
Tazkiyatun nafs is a central concept in Islam that is oriented towards the process of purification and development of the soul as the basis for the formation of Islamic personality. This article aims to conceptually examine the role of tazkiyatun nafs in shaping Islamic personalities that are relevant to Islamic da'wah and counseling practices in the contemporary era. This research uses a qualitative approach with a literature study method through the study of primary and secondary sources, including the Qur'an, hadith, as well as Sufism literature, Islamic psychology, da'wah, and counseling. The results of the study show that tazkiyatun nafs has significant spiritual and psychological implications in shaping self-integrity, emotional balance, and the effectiveness of the da'wah and counseling process. The stages of tazkiyatun nafs which include takhalli, tahalli, and tajalli serve as a framework for self-development that encourages individuals to control negative impulses, internalize noble moral values, and achieve inner peace. Thus, tazkiyatun nafs can be understood as a conceptual as well as a practical foundation in the formation of an Islamic personality that is adaptive to the dynamics and challenges of modern society.